Insect ectoparasites from wild passerine birds in the Czech Republic - Sychra, O; Literák, I; Podzemný, P; Benedikt, V (Parasite (Paris, France), 2008)
Wild passerine birds (Passeriformes) from northeastern part of the Czech Republic were examined for ectoparasites. Three species of louse-flies of the genus Ornithomya (Diptera: Hippoboscidae), two species of fleas of the genera Ceratophyllus and Dasypsyllus (Siphonaptera: Ceratophyllidae), and 15 species of chewing lice belonging to the genera Myrsidea, Menacanthus (Phthiraptera: Menoponidae), Brueelia, Penenirmus, Philopterus (Phthiraptera: Philopteridae) were found on 82 birds of 23 species. New chewing louse-host records are Hippolais icterina for Menacanthus currucae; Motacilla cinerea for Menacanthus pusillus; Turdus philomelos and Motacilla cinerea for Brueelia merulensis; and Sylvia atricapilla for Menacanthus eurysternus. Brueelia neoatricapillae is cited for the first time for the Czech Republic. Parasitological parameters such as prevalence, intensity and abundance are also discussed.
Keywords: Ectoparasitic Infestations; druhová specificita; Male; Česká republika; Animals, Wild; prevalence; divoká zvířata; mužské pohlaví; infestace ektoparazity; zpěvní ptáci; Siphonaptera; Species Specificity; nemoci ptáků; Czech Republic; Animals; Phthiraptera; ženské pohlaví; zvířata; Bird Diseases; Prevalence; Passeriformes; Songbirds; Female; Diptera